Performances of dye-sensitized solar cell (DSSC) with working electrode of aluminum-doped ZnO nanorods - Truly Theresia Saputrina; Iwantono Iwantono; Awitdrus Awitdrus; Akrajas Ali Umar (Lembaga Studi Pendidikan dan Rekayasa Alam Riau, 2020)
Renewable energy sources are intensively developed for substituting fossil energy by several routes, such as solar cells and wind power. As a kind of solar cell, dye-sensitized solar cell (DSSC) was studied for low cost and environmentally friendly cell in competing with a silicon-based cell which dominated in the market. But, main problem in DSSC is low current density and power conversion efficiency, especially zinc oxide (ZnO)-based DSSC. In this paper, we enhance the ZnO nanorod properties through the doping of aluminum (Al). For obtaining optimum results, we varied the dopant concentration of 1%, 1.5%, 1%, and 3%. The Al-doped ZnO nanorod was grown by a seed-mediated hydrothermal method at 90oC for 8 hours. The physical properties were analyzed by field emission scanning electron microscopy and EDX, while the photovoltaic properties were analyzed by J-V curve analysis. An improvement of photovoltaic performance up to 200% is obtained by the ZnO nanorod with 1% Al-doped concentration.